Mouse SAS-6 is required for centriole formation in embryos and integrity in embryonic stem cells - Marta Grzonka; Hisham Bazzi (eLife, 2024)
SAS-6 (SASS6) is essential for centriole formation in human cells and other organisms but its functions in the mouse are unclear. Here, we report that Sass6-mutant mouse embryos lack centrioles, activate the mitotic surveillance cell death pathway, and arrest at mid-gestation. In contrast, SAS-6 is not required for centriole formation in mouse embryonic stem cells (mESCs), but is essential to maintain centriole architecture. Of note, centrioles appeared after just one day of culture of Sass6-mutant blastocysts, from which mESCs are derived. Conversely, the number of cells with centrosomes is drastically decreased upon the exit from a mESC pluripotent state. At the mechanistic level, the activity of the master kinase in centriole formation, PLK4, associated with increased centriolar and centrosomal protein levels, endow mESCs with the robustness in using a SAS-6-independent centriole-biogenesis pathway. Collectively, our data suggest a differential requirement for mouse SAS-6 in centriole formation or integrity depending on PLK4 activity and centrosome composition.